A market for little Caribbean - Kinkead, Gwen, 1951- (SAGE business cases., 2021)
Economic development had come slowly to Little Caribbean, the area tucked south of Prospect Park in Brooklyn. Though it abuts fashionable Park Slope and its West Indian nightclubs attract A-listers, Little Caribbean remains the classic American melting pot of immigrants, hustle, dollar stores, gangs and shootings, underground housing, Mom and Pop outlets, schools and tidy apartment houses. An annual West Indian Day parade celebrates the largest Caribbean community in the nation. Caribbeans replaced the earlier German and Jewish immigrants in the 1970s and now, with African-Americans, East Asians and Hispanics, form the majority of residents. 43 percent of Flatbush's population is foreign-born.Urbane Development, responsible for constructing affordable housing, must decide how to attract a free-spending clientele to build wealth for Flatbush Central's merchants and entrepreneurs without further opening the floodgates to gentrification and rising rents for the local people it aims to bolster. Predatory real estate developers are the enemy in working-class Flatbush, birthplace of Congresswoman Yvette Clarke, Bernie Sanders and actor Michael K. Williams: half its residents are rent-burdened, and 22 percent are impoverished. Tenant organizations fight pitched battles against house flippers and speculators, as in all of gentrifying Brooklyn. How can Urbane build a "world-class retail destination" that anchors economic growth and prevents displacement, in line with its mission to create assets for people of color which stay in their communities?